MORPHOLOGICAL DEVELOPMENT OF THE DIGESTIVE TRACT AT PRE AND POST HATCH PERIOD IN BROILER CHICKS (Gallus gallus domesticus) - Zainab Abbas Mosa; Fawzi Saddam Al-Asadi (University of Thi-Qar Journal of agricultural research, 2022)
The objective of this study was to evaluate the morphological development and growth of different segments of the digestive tract at pre and post hatch period of broiler chickens. A total sixty birds divided into: thirty of embryos at the days 10th , 15th and 20th of incubation period and thirty of chicks at the days 1st , 15th , 30th of post hatch period were used, as ten for each age. The live body weight taken of each bird and after careful evisceration, their digestive tracts segments (esophagus with crop, proventriculus, ventriculus, small intestine and large intestine) were dissected. The location, shape and weight of the collected organs were recorded. Morphological results showed that esophagus divided into two regions by crop cervical esophagus and thoracic esophagus. Stomach was divided into two parts, glandular stomach (proventriculus) and the muscular stomach (ventriculus). Small intestine divided into three parts these are represented by duodenum, jejunum and ileum. Large intestine represented by cecum and colon. Data of the absolute weight of each organ separately, showed increasing with age, were the increasing significantly different between ages (p≤0.05), while the data of the weight of each organ separately relative to body weight showed increasing at pre hatch period and at hatch day, but these values decrease at 15th day of post hatch period.